Tajemnica kobiecego uśmiechu. Rozważania wokół wiersza Stanisława Grochowiaka Nieznajoma z Sekwany i innych tekstów kultury na zajęciach polskiego w liceum (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
The article is a project of literary classes addressed to high school students, devoted to discussing the theme of the Seine drowned woman, a mysterious figure found at the end of the 19th century, whose death mask – due to a delicate smile – became popular all over the world. The story of an anonymous teenager has inspired writers, poets, playwrights, philosophers, painters, architects, and journalists of various times and spaces. She fascinated, among others, Stanisław Grochowiak, Mela Muter, Antoni Kaminski and Aleksander Gierymski, as well as the literary scholar Stanisław Rosiek, who in his article, writing about the importance of death masks in the culture of the nineteenth century, also referred to the figure of the girl.